The Role of Tri Hita Karana–Based Sustainable Human Resource Management in Organizational Performance (A Case Study of Kayoman Pedawa) - Made Supriyani; Ni Made Ary Widiastini (Universitas Muhammadiyah Pontianak, 2026)
This study investigates how sustainable human resource management (HRM) inspired by Tri Hita Karana (THK) shapes the organizational performance of the Kayoman Pedawa community. Using a qualitative ethnographic design, this research collected data through participant observation, in-depth interviews, and documentation, which were analyzed thematically across parahyangan, pawongan, and palemahan. Findings show that HRM is manifested as social solidarity in recruitment (pawongan), spiritual motivation through rituals (parahyangan), and ecological responsibility via conservation practices (palemahan). The study argues that the sustainability of community-based organizations in Bali depends on integrating modern management practices with local philosophical values.